FENOMENA PENUNDAAN PERNIKAHAN PADA GENERASI Z AKIBAT ORIENTASI PENGEMBANGAN DIRI: KAJIAN HUKUM KELUARGA ISLAM - Achmad Adnan; Teguh Dwi Cahyadi (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The self priority phenomenon has shifted Generation Z's marriage readiness from spiritual-collective values toward psychological-materialistic standards driven by social media pressure. This normative legal research aims to analyze this phenomenon using a conceptual approach and a maqasid al-syari‘ah perspective. The findings indicate that delaying marriage for education and career pathways yields substantial benefits based on the maxim of averting harm. Through the maqasid al-syari‘ah framework, this self prioritization fulfills the pillars of hifz al-din (spirituality), hifz al-nafs (mental health), hifz al-nasl (lineage), and hifz al-mal (wealth) to minimize divorce risks. Theoretically, this study aligns the transition characteristics of emerging adulthood by formulating "Contemporary Pre-Marital Jurisprudence based on Self-Actualization." Practically, it recommends a new counseling model within the KUA that integrates a digital literacy curriculum (digital relationship wellbeing) and pre-marital mental health screening to foster adaptive family resilience.